Optimizing plant spatial competition can change phytohormone content and promote tillering, thereby improving wheat yield - Liu, Pan; Yin, Baozhong; Liu, Xuejing; Gu, Limin; Guo, Jinkao; Yang, Mingming; Zhen, Wenchao (Frontiers in Plant Science, 2023)
As an important manner of inter-plant competition, line-spacing shrinkage and row-spacing expansion (LSRE) can cause wheat to form an increased number of tillers and improve resource utilization efficiency. Wheat tillering is closely related to a variety of endogenous hormones. However, whether LSRE treatment regulates changes in endogenous hormones and their relationship with wheat tillering and yield is largely unknown. In this study, the tillering characteristics, hormone content in tiller nodes at the pre-winter stage, and yield factors were evaluated for the winter wheat variety Malan1. We used a two-factor randomized block trial design with two sowing spacings of 15 cm (15RS, conventional treatment) and 7.5 cm (7.5RS, LSRE treatment) at the same density and three sowing dates (SD1, SD2, and SD3). LSRE significantly promoted wheat tillering and biomass at the pre-winter stage (average increases of 14.5% and 20.9% at the three sowing dates, respectively) and shortened the accumulated temperature required for a single tiller. Changes in the levels of phytohormones, including decreased gibberellin and indole acetic acid and increased zeatin riboside and strigolactones, were detected using high-performance liquid chromatography and shown to be responsible for the tillering process under LSRE treatment in winter wheat. LSRE treatment can improve crop yield by increasing the number of spikes per unit area and grain weight. Our results clarify the changes in tillering and endogenous hormone content of winter wheat under LSRE treatment and their correlation with grain yield. This study also provides insight into the physiological mechanism of alleviating inter-plant competition to improve crop yield.